A Jeopardy-Style Review Game Using Team Clickers - John Cusick (Association of American Medical Colleges, 2016)
Abstract Introduction Gaming has been used for many years as a useful supplemental instruction method in the biomedical sciences. However, the effective use of games can be challenging in a large classroom setting due to the difficulty of engaging all students. The goal of this exercise was to design an interactive way to review material that promoted small-group discussion in a large class of 104 students. A review game comparable to Jeopardy was utilized that enabled small teams to engage in friendly competition, using team clickers and a team leaderboard that tracked the team scores in a lowstakes, fun environment. Methods Individual team clickers were used with a Jeopardy-style review game. TurningPoint served as the audience response system. Nineteen preassigned teams comprised of five to six students per team considered all questions during the closed-book review game. Discussion within teams was encouraged prior to each team's selection of an answer using the team clicker. A team leaderboard tracking the team scores was periodically displayed throughout the exercise, which helped keep the students engaged in a fun and relaxed atmosphere, as no extra points were awarded to the winning team. Results The review game was enthusiastically received by the students and was frequently cited as an aspect the students enjoyed most about the course. The review game was also positively received by both pharmacy faculty and medical school faculty of the university when presented as a teaching tool during a faculty development session. Discussion Although this resource was intended to serve as a serious game to review immunology topics for third-year pharmacy students, it can be used to teach a variety of science topics within the medical education setting. Similarly, while this review game was used within the context of team-based learning pedagogy, it can also be used in a traditional classroom setting, with preassigned teams for the review game.